Congenital syphilis confirmed by PCR as a result of treatment failure for syphilis in pregnancy. Case report - Mery Yolanda Cifuentes Cifuentes; Linda Stefany Gómez Aristizábal; Gladys Pinilla Bermúdez; Claudia Cruz; Jeannette Navarrete (Case Reports)
Introduction: Congenital syphilis is a major public health problem, and early diagnosis and treatment are necessary to prevent it. Penicillin G benzathine is the treatment of choice in pregnant women; however, it may fail to prevent fetal infection, as in the present case.